2016
DOI: 10.1074/jbc.m115.698530
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Expression of the Small Heat Shock Protein αB-Crystallin Inhibits Exosome Secretion in Human Retinal Pigment Epithelial Cells in Culture

Abstract: Exosomes carry cell type-specific molecular cargo to extracellular destinations and therefore act as lateral vectors of intercellular communication and transfer of genetic information from one cell to the other. We have shown previously that the small heat shock protein ␣B-crystallin (␣B) is exported out of the adult human retinal pigment epithelial cells (ARPE19) packaged in exosomes. Here, we demonstrate that inhibition of the expression of ␣B via shRNA inhibits exosome secretion from ARPE19 cells indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…In order to further our understanding regarding the function of αB-crystallin upregulation, we next used shRNA to knock-down its expression. Treatment of oligodendrocyte cultures with lentiviral particles carrying shRNA constructs previously demonstrated to reduce αB-crystallin expression (Gangalum, Bhat, Kohan, & Bhat, 2016) similarly reduced expression of αB-crystallin in cultures which were treated with EAE sera (Figure 6k). Cell survival of lentiviral-transfected oligodendrocyte cultures was then assayed following exposure to sera.…”
Section: Passive Transfer Of Sera Results In αB-crystallin Upregulasupporting
confidence: 80%
“…In order to further our understanding regarding the function of αB-crystallin upregulation, we next used shRNA to knock-down its expression. Treatment of oligodendrocyte cultures with lentiviral particles carrying shRNA constructs previously demonstrated to reduce αB-crystallin expression (Gangalum, Bhat, Kohan, & Bhat, 2016) similarly reduced expression of αB-crystallin in cultures which were treated with EAE sera (Figure 6k). Cell survival of lentiviral-transfected oligodendrocyte cultures was then assayed following exposure to sera.…”
Section: Passive Transfer Of Sera Results In αB-crystallin Upregulasupporting
confidence: 80%
“…In early AMD, the RPE is thought to contribute to the formation of drusen (extracellular material that builds up between the RPE and Bruch’s membrane). Wang et al, had proposed that exosomes released from aged RPE might contribute to the formation of drusen [50], and polarized release of exosomes from RPE cells has been described in cultured RPE cells [39, 82, 83]. In addition to damaging effects, exosomes released from the RPE are also thought to contribute to neuroptrotection in the retina [84].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both heparanase and syndecan-1 are involved in exosome biogenesis and regulation of exosome release (Thompson et al, 2013). Furthermore, a recent study by Gangalum and colleagues (Gangalum et al, 2016) reported that shRNA knockdown of αB-Crystallin in ARPE-19 cells severely inhibits both apical and basolateral exosome and/or small EV release. Thus, approaches attempting to regulate exosome release in the affected cell types, as well as targeting proteoglycans found on exosomes and in the ECM of the retinal vasculature and BrM at the choriocapillarismay be able to reduce neovascularization in neovascular AMD and diabetic retinopathy.…”
Section: Exosomes In Ocular Angiogenesismentioning
confidence: 99%
“…An exhaustive characterization of EVs released both apically and basolaterally from RPE cells under normal and pathophysiological conditions is critical to elucidating the potential role of exosomes in the AMD disease process. Interestingly, a recent study showed that under serum-free conditions of exosome collection from polarized ARPE-19 cultures, the total exosome release was about twofold higher on the apical vs basolateral side (Gangalum et al, 2016). Our own studies using polarized primary RPE cultures show similar results under FBS-supplemented culture conditions.…”
Section: Exosomes and Extracellular Matrix (Ecm)mentioning
confidence: 99%